Idaarati Manaahij Al-Lughah Al-‘Arabiyah bi Indonesia - Azimah, Hanifa (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2025)
This paper aims to describe the management of the Arabic curriculum, especially nahwu, at the Tahfiz Muallimin Muhammadiyah Sawah Dangka Islamic Boarding School, its positive and negative sides and its development suggestions. This study uses a descriptive qualitative method. The results of this study show the implementation of Arabic curriculum management at the Tahfiz Muallimin Muhammadiyah Sawah Dangka Islamic Boarding School using the nazhariyah furu' system. The book